Integrasi Bank Syariah Indonesia dan Implikasinya Terhadap Pengembangan Ekonomi Syariah - Ima Ismawati; Maria Yosepha; Dedy Kartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the Bank Syariah Indonesia (BSI) integration policy, a strategic step taken by the government to strengthen the national Islamic banking structure to address the challenges of financial stability, global competitiveness, and sustainable Islamic economic development. This study aims to analyze the implications of BSI institutional integration on strengthening the Islamic banking system, financing the real sector, and transforming governance and digitalization to support the national Islamic economy. The research method used is qualitative with a descriptive approach through a literature review of scientific journals, academic books, and relevant official reports. The research findings indicate that BSI integration has a positive impact on increasing business scale, strengthening capital, operational efficiency, and optimizing risk management, which contributes to the stability of the Islamic financial system and global competitiveness. Furthermore, integration strengthens the intermediation function of Islamic finance by increasing the financing capacity of the real sector, particularly MSMEs, expanding profit-sharing contracts, and accelerating financial inclusion through digitalization. The research findings also confirm that the success of integration is largely determined by the synergy between Sharia governance and compliance, the use of digital technology, and effective change management based on leadership and alignment of organizational culture. The implications of this research indicate that BSI integration not only strengthens Islamic banking institutions but also serves as an important foundation for the development of a just, inclusive, and sustainable national Islamic economy.